2017
DOI: 10.1038/s41598-017-03736-3
|View full text |Cite|
|
Sign up to set email alerts
|

Uniting the neurodevelopmental and immunological hypotheses: Neuregulin 1 receptor ErbB and Toll-like receptor activation in first-episode schizophrenia

Abstract: Current pathophysiological models of schizophrenia focus on neurodevelopmental and immunological mechanisms. We investigated a molecular pathway traditionally linked to the neurodevelopmental hypothesis (neuregulin 1 - ErbB), and pathogen-associated pattern recognition receptors associated with the immune hypothesis (Toll-like receptors, TLRs). We recruited 42 first-episode, drug-naïve patients with schizophrenia and 42 matched healthy control subjects. In monocytes TLR4/TLR5 and ErbB expressions were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…Thus, NRG2 may play a role in the pathophysiology of schizophrenia but based on our results seems less likely to serve as a peripheral marker of neurobiological changes found in schizophrenia. Likewise, ErbB2 mRNA expression seems an unlikely peripheral marker of schizophrenia based on our null findings as well as findings from others that reported no difference in ErbB2 mRNA expression in monocytes of first-episode, drug-naive patients with schizophrenia compared to healthy controls ( 48 ). However, this same study suggested that there may be an exaggerated NRG1 stimulated cytokine response from PBMC in people with schizophrenia compared to controls ( 48 ), suggesting a link between overactive NRG1 signaling and inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, NRG2 may play a role in the pathophysiology of schizophrenia but based on our results seems less likely to serve as a peripheral marker of neurobiological changes found in schizophrenia. Likewise, ErbB2 mRNA expression seems an unlikely peripheral marker of schizophrenia based on our null findings as well as findings from others that reported no difference in ErbB2 mRNA expression in monocytes of first-episode, drug-naive patients with schizophrenia compared to healthy controls ( 48 ). However, this same study suggested that there may be an exaggerated NRG1 stimulated cytokine response from PBMC in people with schizophrenia compared to controls ( 48 ), suggesting a link between overactive NRG1 signaling and inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, other major pathways that are predicted to be affected by such an integrated change in gene expression in the frontal pole from subjects with Sz are those regulated by oestrogen, serotonin, acetylcholine and neuregulin 1 and there is extensive evidence to implicate these pathways are involved in the pathophysiology of the disorder. 52 55 In addition, oestrogen, 56 , 57 serotonin, 58 acetylcholine 59 , 60 and neuregulin 1 61 are known to control both developmental and inflammatory pathways, two overarching pathways likely to be affected by changes in expression of genes in the frontal pole interactome.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increased TLR4 signaling maintains NF-κB and MAPK/ErK (Venkatasubramanian and Debnath, 2013; García-Bueno et al, 2016; McKernan et al, 2011). Since both proteins can phosphorylate CaMKIIα, an increased TLR4 signaling can negatively regulate CaMKIIα expression and increase synaptic dysfunction in schizophrenia (Kéri et al, 2017). In addition to reducing CaMKIIα-linked NMDAR current, MAPK/ErK can also phosphorylate pore forming subunits of potassium channels (Barros et al, 2012; Gustina and Trudeau, 2011; Schrader et al, 2006; English and Sweatt; 1997; Selcher et al, 2003) thereby contributing to synaptic dysfunction.…”
Section: Discussionmentioning
confidence: 99%